Midwives’ therapeutic communication to treat antenatal depression - Dianingtyas Putri; Suharyanti Suharyanti; Eirenne Elisabeth Putri (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2025)
The maternal mortality rate (MMR) and child mortality rate in Indonesia are among the highest in ASEAN (Association of Southeast Asian Nations), ranking 7th out of 10 ASEAN countries. One of the contributing factors is complications during pregnancy and childbirth, in addition to economic, social, and psychological conditions. This situation leads to antenatal depression during pregnancy, highlighting the crucial role of midwives in providing holistic support. The current research investigates the role of midwives in pregnancy using therapeutic communication in tackling the phenomenon of maternal and child mortality. Results indicated that in the pre-interaction, orientation, working, and termination phases, the informants experienced different outcomes that further affected their self-efficacy about those stages.